2019
DOI: 10.1111/ijfs.14263
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation kinetics of carotenoids, vitamin C and provitamin A in tree tomato juice

Abstract: SummaryIn this research, the influence of temperature on the degradation of carotenoids, vitamin C and provitamin A in tree tomato juice was studied at 70, 80 and 90 °C. The thermal processing significantly reduced (P < 0.001) the concentration of the bioactive compounds, and the thermal degradation in the evaluated phytochemicals fit a kinetic first order, with the following activation energies (Ea, kJ mol−1): α‐carotene (69.75), β‐carotene (59.50), provitamin A (51.67), zeaxanthin (43.66), vitamin C (41.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
7
20
2
Order By: Relevance
“…These degradations of TPC and AAC followed the first order model (with R 2 >0.91) as well as the Arrhenius model (with R 2 >0.93). As expressed in Table 3, the specific k value ranged from 0.0018 to 0.0050 for TPC, and from 0.0014 to 0.0056 for AAC, for the temperature range from 70 o C to 90 o C. The previous studies also found the same behaviour on tomato, strawberry, raspberry, marula, guava, and mango juices during thermal treatment [29][30][31][32].…”
Section: Kinetic Degradation Of Ascorbic Acid and Total Phenolic Cont...supporting
confidence: 54%
“…These degradations of TPC and AAC followed the first order model (with R 2 >0.91) as well as the Arrhenius model (with R 2 >0.93). As expressed in Table 3, the specific k value ranged from 0.0018 to 0.0050 for TPC, and from 0.0014 to 0.0056 for AAC, for the temperature range from 70 o C to 90 o C. The previous studies also found the same behaviour on tomato, strawberry, raspberry, marula, guava, and mango juices during thermal treatment [29][30][31][32].…”
Section: Kinetic Degradation Of Ascorbic Acid and Total Phenolic Cont...supporting
confidence: 54%
“…Hot drying provides very different results from the other two drying procedures, although the averages of the ΔH* are similar: alteration of H* is highly dependent on maturity degree ( Table 1 ); it is low for ripe mangoes and high for immature mangoes. Since there is a large increase in carotenoid content during ripening, the increase in reaction rate as a function of temperature [ 42 ] should be more visible in ripe mangoes, i.e., those rich in carotenoids, than in less mature mangoes.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies on the degradation kinetics of organic compounds during thermal processing in food science. The degradation kinetic in the thermal process is generally in line with a zero-order or first-order kinetic reaction model [ 26 , 27 ]. Therefore, zero-order and first-order kinetic formulae were used to describe the thermal degradation of IPBC in this study.…”
Section: Methodsmentioning
confidence: 99%